A study on the clinical effectiveness of a tiered management model for type 2 diabetes based on a three-level linkage mechanism in the context of residency training: a randomized controlled trial - Wu, Silin; Liu, Tinglian; Chen, Lan; Wang, Min; Deng, Jieyin; Qin, Yang (Frontiers in Endocrinology, 2025)
BackgroundWith the widespread implementation of General Practice Residency Training (GPRT) in China, primary care institutions have enhanced chronic disease management capabilities. However, research on tiered management for type 2 diabetes mellitus (T2DM), particularly systematic exploration based on a three-tier collaborative model (primary-secondary-tertiary institutions), remains limited.ObjectiveTo evaluate the clinical effectiveness of a three-tiered linkage hierarchical management model for T2DM implemented within the GPRT framework.MethodsThis study enrolled 120 T2DM patients from a community-based GPRT site (followed February-November 2024). Stratified by clinical risk factor, patients were randomly assigned (computer-generated sequence, allocation concealed) to an intervention group (n=60) or control group (n=60). The intervention group received tiered management via an“Internet+”platform(telemedicine)coordinated by multidisciplinary teams (general practice residents, mentors, specialists). The control group received standard community care. Fasting blood glucose (FPG), 2-hour postprandial blood glucose (2h-PBG), glycated hemoglobin (HbA1c), and the Summary of Diabetes Self-Care Activities (SDSCA) scale were assessed at baseline, 3, and 6 months.ResultsBaseline characteristics, FPG, 2h-PBG, and HbA1c were comparable (P > 0.05). Post-intervention, the intervention group exhibited significantly greater reductions in FPG, 2h-PBG, and HbA1c than the control group (P < 0.05). SDSCA scores indicated superior improvements in key domains (diet, exercise, blood glucose monitoring, foot care) for the intervention group (P < 0.05). Medium- and high-risk subgroups within the intervention group achieved significantly better glycemic control than their control counterparts (P < 0.05), with no significant difference observed in the low-risk subgroup (P > 0.05).ConclusionThe three-tiered linkage management model under GPRT significantly improves glycemic control and self-management in T2DM patients. Integrating multidisciplinary teamwork and digital tools, the model’s structure demonstrates effectiveness within the community setting and exhibits potential for wider implementation in broader healthcare contexts, offering valuable policy implications for optimizing chronic disease management.Clinical Trial Registrationhttps://www.chictr.org.cn/index.html, identifier ChiCTR2500100827.